Antibiofilm activity in vitro of Rosmarinus officinalis and Syzygium cumini glycolic extracts on Staphylococcus spp. of dentistry interest - Freire, Fernanda; Pereira, Cristiane Aparecida; Oliveira, Luciane Dias; Junqueira, Juliana Campos; Jorge, Antonio Olavo Cardoso (Brazilian Dental Science, 2017)
Objective: The aim of this study was to identify the slime production and evaluate the effects of Rosmarinus officinalis (rosemary) and Syzygium cumini (jambolan) glycolic extracts, and 0.12% chlorhexidine (CHX) in biofilms formed by strains of coagulase-positive Staphylococcus - CPS and coagulase negative Staphylococcus - CNS isolated from the oral cavity. Material and Methods: Slime production was evaluated by two methods: the color of colony presented in Congo red agar, and through the amount of slime adhered to polystyrene. Biofilms were grown in acrylic resin discs immersed in broth, inoculated with microbial suspension (106 cells/ml) and incubated at 37°C/48 h. After formation, the biofilms were exposed for 5 minutes to glycol extracts, CHX or saline solution. The viability of biofilms was determined by counting the colony-forming units per milliliter (CFU/ml) in agar, and analyzed statistically by Tukey test (p